Installing a More Coercive Senate for Enhanced Fiscal Capacity within the Counties of Kenya - Mungai, Melissa (Strathmore Law Review, 2017)
The clamour to divest the Kenyan parliament of its senate has been championed by a handful of critics who describe this parliamentary house as weak and a burden to taxpayer money. The root of such conclusions could be that the senate has legislative power that is less clear than that of the national assembly. With clearer and enhanced authority, the senate will be able to carry out its function of representing county interests at the national level effectively, more so with regard to the vertical and horizontal allocation of revenue. This paper seeks to make an argument in favour of the senate by illustrating its significant role as the custodian of devolution in Kenya and more specifically in the building of county fiscal capacity.